The impact of family of origin on social workers from alcoholic families and implications for practice : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University - Coombes, Karenza Anne (Massey University, 1998)
Social work education and social work practitioners involved in intervention in the lives of families, have long recognised that prior life experience impacts on their work. However, little research appears to have been carried out in this area, particularly in New Zealand. The current study is an attempt to redress this situation on a small scale by exploring with a group of six (6) social workers who are adult children of alcoholics (ACoA), their understanding of their family of origin experience and its effect on their current practice. The present study is an exploratory one, drawn from the life histories of six social workers, who have identified themselves as growing up in an alcoholic family. Based on the perceptions of the social workers involved, and an understanding of the relationship between their life history and how they practice, the project explores the concepts and themes that emerged within the study and the connections between them including the similarities and differences. Findings suggest that although participants have experienced the conflict, trauma, physical and emotional abuse commonly found in families with alcoholic parents, they have shown themselves to have a capacity for successful adaptation, positive functioning and competence. These factors have been identified conceptually as resiliency. The impact of these protective factors as well as the cost of resiliency appeared relevant to the participants and to their social work practice. These findings align with previous theory and research, particularly in regard to the importance of the triad of protective factors individual, family and environmental. Further, as the research developed, the relevance of the theory of attachment became significant. Findings in this area indicated that despite their generally abusive backgrounds, participants had formed early positive attachments which similarly influenced subsequent interpersonal relationships. The outcomes of this research give rise to questions for further research by social workers, other professionals and educators wanting to examine the possible impact of family of origin experience, particularly for the children of alcoholic families, upon social service practitioners and their practice.
Keywords: Social workers; Family relationships; New Zealand; Children of alcoholics